Exchange Rate Arrangements and Currency Convertibility : Developments and Issues - Johnston, R. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1999)
This study reviews the developments and issues in the exchange arrangements and currency convertibility of IMF members. The principal information source for this report is the Annual Report on Exchange Arrangements and Exchange Restrictions prepared in consultation with national authorities.